Relationship between the surface chemical composition of implants and contact with the substrate - Valente, Mariana Lima da Costa; Shimano, Antonio Carlos; Marcantonio Júnior, Elcio [UNESP]; Reis, Andréa Cândido dos (American Academy of Implant Dentistry, 2015)
The purpose of the study was to use scanning electron microscopy and energy dispersive x-ray spectrometry to assess possible morphologic and chemical changes after performing double-insertion and pullout tests of implants of different shapes and surface treatments. Four different types of implants were used—cylindrical machined-surface implants, cylindrical double-surface–treated porous implants, cylindrical surface-treated porous implants, and tapered surface-treated porous implants—representing a total of 32 screws. The implants were inserted into synthetic bone femurs, totaling 8 samples, before performing each insertion with standardized torque. After each pullout the implants were analyzed by scanning electron microscopy and energy dispersive x-ray spectrometry using a universal testing machine and magnified 35 times. No structural changes were detected on morphological surface characterization, only substrate accumulation. As for composition, there were concentration differences in the titanium, oxygen, and carbon elements. Implants with surface acid treatment undergo greater superficial changes in chemical composition than machined implants, that is, the greater the contact area of the implant with the substrate, the greater the oxide layer change. In addition, prior manipulation can alter the chemical composition of implants, typically to a greater degree in surface-treated implants.